The Effect of Workplace Spirituality, Perceived Organizational Support, and Innovative Work Behavior: The Mediating Role of Psychological Well-Being - Masyhuri Masyhuri; Pardiman Pardiman; Siswanto Siswanto (Universitas Hayam Wuruk Perbanas, 2021)
This research investigating the innovative work behavior of teachers and school staff during the Covid-19 pandemic is still rarely studied, so it has contributed to improving the behavior of teachers and school staff in Indonesia during the Covid-19 pandemic. The purpose of this study was to analyze and examine the direct influence of workplace spirituality and perceived organizational support on the innovative work behavior of teachers and school staff. Besides, exploring the mediating role of psychological health variables. The research sample was 379 teachers and school staff that is analyzed using SEM-PLS. The results showed that workplace spirituality and perceived organizational support had a direct effect on innovative work behavior.Psychological well-being also affects innovative work behavior. This study also shows that psychological well-being has a role in mediating the influence between work-place spirituality and perceived organizational support for innovative work behavior. This study indicates that workplace spirituality and workplace spirituality can be directly and indirectly through psychological well-being to increase the innovative behavior of teachers and school staff in learning activities at school.